Need for consistent beach lifeguard data collection: results from an international survey. Issue 4 (31st July 2020) - Koon, William; Schmidt, Andrew; Queiroga, Ana Catarina; Sempsrott, Justin; Szpilman, David; Webber, Jonathon; Brander, Robert
Abstract : Background: Lifeguards are integral to beach safety and collect data which is used for a variety of purposes, although guidelines and best practice have yet to be established. This study served to identify and characterise existing beach lifeguard service provider (BLSP) data collection procedures in order to identify the degree of uniformity and areas for improvement. Methods: The 'International Beach Lifeguard Data Collection and Reporting' online survey was distributed via the International Drowning Researchers' Alliance to BLSP supervisors and managers. The survey included questions on beach conditions and lifeguard activity data collection practices, and respondent's opinions on their own BLSP's methods. Results: Variability in data collection practices was evident in surveys obtained from 55 lifeguard leaders in 12 countries. Discrepancies exist in definitions for 'rescue' among BLSPs, a significant amount of information related to beach conditions are recorded and beach visitation is primarily obtained by visual estimate. Respondents expressed challenges with getting frontline staff to collect information in the field and ensuring reporting consistency between recorders. They identified rescue victim demographic factors as key data they would like to collect in the future. Conclusions: Inconsistencies in lifeguard data collection present challenges to operations, safety education and prevention efforts, research and policy relying on these data. Variation in definitions, methods and collected variables generally restricts analysis to a single BLSP with limited generalisability to other beach settings. Some gaps in lifeguard data collection may soon be addressed by technology, but developing uniform, internationally acceptable standards and definitions should be prioritised.